(untitled) (Altre Modernità, 2013)
The myth of Urakán, the great god of the Antilles, reveals a certain persistence in Cuban literature and in Alejo Carpentier’s production ever since his first text (1917), which was a “pequeña prosa” about the importance of Caribbean cyclone (Alejo Carpentier, Entrevistas, La Habana, Letras cubanas, 1985: 254). This theme, actually, both in his ethical and aesthetic aspects, will recur frequently in his work, with the symbolic and contradictory connotation of Apocalypses.